THE EFFECT OF APPLYING COOPERATIVE LEARNING MODEL WITH MIND MAP AS A HOMEWORK ON NATURAL SCIENCE COMPETENCE: LITERATURE STUDY - Widya Verina Tanjung; Lufri Lufri (Universitas Negeri Padang, 2021)
Mind mapping is a creative and effective note taking technique, with a Mind Map can store information in the brain and make learning easier. Cooperative learning is a learning model divides student into groups. Coopeartive learning make a student to be active in the learning process. The purpose of this study was to obtain a description of the effect using a Mind Map with cooperative learning models on the learning science competence of students. This research is ex-post facto research. The data use secondary data, namely data sourced from scientific journal articles. Data collection techniques in this study are documentation technique, data analysis in the form of content analysis. The step used in this research are exploring ideas, looking for information, emphasizing the materials used, looking for reading materials, reorganizing the material back and writing the research result. The literature result showed that therewas a positive effect on the use of Mind Map with cooperative learning models on the science competence. The use of Mind Map with cooperative learning models can make student can store information in a creative and effective way, and can make a student more active in the learning process.